Ejecta curtain radiative transfer modeling for probing its geometry and dust optical properties. (October 2015) - Shalima, P.; Wada, K.; Kimura, H.
Abstract: An ejecta curtain is produced as a result of impact cratering of celestial bodies that excavates and ejects their surface and underground material. Since ejecta particles are thought to reflect the interior materials and structures of celestial bodies, ejecta and ejecta curtains provide us with valuable information about the interior of the bodies. Following the Deep Impact mission, more and more in situ data on ejecta curtains are expected to become available in future space missions. To draw valuable information from such in situ measurements, a radiative-transfer model of the ejecta curtain plays an important role. This urges us to carefully assess the model parameters with experimental results as well as understand the contribution of each model parameter to the predicted intensities of the radiative calculations. In this work, we study the dependences of the projected intensity images of the ejecta on the scattering phase function and the geometry of an ejecta curtain produced by impact on an airless-body's surface, as a first step toward a correct interpretation of ejecta observations. Using the Monte-Carlo multiple scattering method, we have calculated the scattered intensities for three different orientations of the ejecta curtain. We have also computed the intensities for ejecta material using different phase functions. We find that the scattered intensities are highest for the isotropic phase function irrespective of the orientation of the ejecta cone for the scattering angles and geometry considered here. Observations from the other side could lead to higher intensities for forward scattering grains that are typical for asteroids. Therefore in situ observations of ejecta-curtains at different angles will enable us to use our model predictions to extract the phase functions as well as column densities of its component dust grains. Abstract : Highlights: Scattering of light by the ejecta curtains produced by impacts on cosmic bodies is considered. The Monte-Carlo multiple scattering approach was used to simulate light-scattering. The dependence of the model intensities on the phase function of the ejecta and the scattering properties of dust grains is studied.